Inventory of methane and nitrous oxide emissions from freshwater aquaculture in China - Liangliang Zhang; Xuhui Wang; Ling Huang; Chenzhi Wang; Yuanyi Gao; Shushi Peng; Josep G. Canadell; Shilong Piao (Communications Earth & Environment, 2024)
Abstract Aquaculture is a major emission source of atmospheric methane (CH4) and nitrous oxide (N2O). However, its contribution remains highly uncertain because the source has been neglected in global and national greenhouse gas inventories. Here, we present an inventory of CH4 and N2O fluxes from five freshwater aquaculture systems in China, which accounted for more than half of global freshwater aquaculture production during 2000-2020. We show that total CH4 and N2O emissions were 2.5 (0.6-4.2) Tg CH4 yr-1 and 18.3 (3.8-32.2) Gg N2O yr-1, respectively, with 75% coming from ponds and paddy fields. CH4 and N2O effluxes from freshwater aquaculture were 5 and 2 times higher than the average from other inland water bodies, respectively. Aquaculture accounts for half of the national inland water emissions, and outweighs the land soil methane sink. We suggest that tracking aquacultural emissions and their reduction through aerated systems could provide additional opportunity to reduce agricultural non-CO2 emissions without compromising food security.